Widespread non-joint pain in early rheumatoid arthritis. (4th July 2021) - Schelin, MEC; Westerlind, H; Lindqvist, J; Englid, E; Israelsson, L; Skillgate, E; Klareskog, L; Alfredsson, L; Lampa, J
Abstract : Objective : The aim of the study was to assess the development of widespread non-joint pain (WNP) in a cohort of patients with early rheumatoid arthritis (RA), the associated health-related quality of life (HRQoL), and clinical and demographic risk factors for WNP. Method : Incident cases with RA, from the Swedish population-based study Epidemiological Investigation of Rheumatoid Arthritis (EIRA), with a follow-up of at least 3 years, constituted the study population. WNP was defined as pain outside the joints in all four body quadrants and was assessed at the 3 year follow-up. Patients who reported WNP were compared to patients without WNP regarding HRQoL, measured by the Short Form-36, at 3 years, and clinical and demographic characteristics at the time of RA diagnosis. Results : A total of 749 patients constituted the study sample, of whom 25 were excluded after reporting already having severe pain before RA diagnosis. At the 3 year follow-up, 8% of the patients reported having WNP as well as statistically significant worse HRQoL. At the time of RA diagnosis, the patients with WNP had worse pain and pain-related features, while no difference was seen in the inflammatory parameters. Conclusion : WNP occurs in a substantial subset of patients with RA, also early in the course of the disease, and the HRQoL for these patients is significantly reduced. Patients who develop WNP at 3 years are already distinguishable at the time of diagnosis by displaying more pronounced pain ratings together with an average level of inflammatory disease activity.